A large benign phyllodes tumour of the breast: A case report and literature review. (2017) - Yan, Zhiyan; Gudi, Mihir; Lim, Swee Ho
Highlights: Phyllodes is an uncommon tumour of the breast that should be considered in the middle age women with a rapidly enlarging breast mass. There is no hallmark imaging characteristic of phyllodes tumour. It is difficult to diagnose phyllodes based on a core biopsy due to the subjective nature of interpretation of the degree of stromal cellularity and degree of atypia. Even if a phyllodes is diagnosed on core biopsy, an excision biopsy is always required to determine if it is a benign or malignant phyllodes tumour. Complete systemic review of patient is important as in this case report, the patient's malignant parotid tumour was diagnosed when she presented with her benign phyllodes tumour. Abstract: Introduction: Phyllodes tumours are uncommon fibroepithelial lesions that typically grow up to 4 cm in size but 10 cm tumours known as giant phyllodes tumours have been described. We present a case report of a 20 cm benign phyllodes tumour and a literature review. Presentation of case: A 54 years old lady with an enlarging left breast mass measuring 20 cm of 6 months duration presented to our outpatient breast clinic. She also had an incidental right parotid lump. Core biopsy of the left breast mass returned as a cellular fibroepithelial lesion. A mastectomy and axillary lymph node sampling were done and skin cover was obtained from a split skin graft from the thigh. Final histology returned as a benign phyllodes tumour. Her post-operative recovery was uneventful. Discussion: Phyllodes tumours are suspected in middle age women with rapidly enlarging painless breast masses. Though there are some suggestive features on ultrasound and MRI, the key to diagnosis is still histopathology. However, a pre-operative diagnosis may not always be possible as the interpretation of stromal cellularity and degree of atypia needed to differentiate cellular fibroadenoma from a phyllodes tumour is subjective. When a phyllodes tumour is suspected, adequate margins should be taken for optimal outcome. Conclusion: Successful management of phyllodes tumour involves obtaining a pre-operative diagnosis via a core biopsy when possible and planning for adequate margins.